Asthma inflammatory phenotypes on four continents: most asthma is non-eosinophilic. (30th August 2022) - Pembrey, Lucy; Brooks, Collin; Mpairwe, Harriet; Figueiredo, Camila A; Oviedo, Aida Y; Chico, Martha; Ali, Hajar; Nambuya, Irene; Tumwesige, Pius; Robertson, Steven; Rutter, Charlotte E; van Veldhoven, Karin; et al.
Abstract: Background: Most studies assessing pathophysiological heterogeneity in asthma have been conducted in high-income countries (HICs), with little known about the prevalence and characteristics of different asthma inflammatory phenotypes in low-and middle-income countries (LMICs). This study assessed sputum inflammatory phenotypes in five centres, in Brazil, Ecuador, Uganda, New Zealand (NZ) and the United Kingdom (UK). Methods: We conducted a cross-sectional study of 998 asthmatics and 356 non-asthmatics in 2016–20. All centres studied children and adolescents (age range 8–20 years), except the UK centre which involved 26–27 year-olds. Information was collected using questionnaires, clinical characterization, blood and induced sputum. Results: Of 623 asthmatics with sputum results, 39% (243) were classified as eosinophilic or mixed granulocytic, i.e. eosinophilic asthma (EA). Adjusted for age and sex, with NZ as baseline, the UK showed similar odds of EA (odds ratio 1.04, 95% confidence interval 0.37–2.94) with lower odds in the LMICs: Brazil (0.73, 0.42–1.27), Ecuador (0.40, 0.24–0.66) and Uganda (0.62, 0.37–1.04). Despite the low prevalence of neutrophilic asthma in most centres, sputum neutrophilia was increased in asthmatics and non-asthmatics in Uganda. Conclusions: This is the first time that sputum induction has been used to compare asthma inflammatory phenotypes in HICs and LMICs. Most cases were non-eosinophilic, including in settings where corticosteroid use was low. A lower prevalence of EA was observed in the LMICs than in the HICs. This has major implications for asthma prevention and management, and suggests that novel prevention strategies and therapies specifically targeting non-eosinophilic asthma are required globally.